Repeat-based holocentromeres of the woodrush Luzula sylvatica reveal insights into the evolutionary transition to holocentricity - Yennifer Mata-Sucre; Marie Krátká; Ludmila Oliveira; Pavel Neumann; Jiří Macas; Veit Schubert; Bruno Huettel; Eduard Kejnovský; Andreas Houben; Andrea Pedrosa-Harand; Gustavo Souza; André Marques (Nature Communications)
Abstract In most studied eukaryotes, chromosomes are monocentric, with centromere activity confined to a single region. However, the rush family (Juncaceae) includes species with both monocentric (Juncus) and holocentric (Luzula) chromosomes, where centromere activity is distributed along the entire chromosome length. Here, we combine chromosome-scale genome assembly, epigenetic analysis, immuno-FISH and super-resolution microscopy to study the transition to holocentricity in Luzula sylvatica. We report repeat-based holocentromeres with an irregular distribution of features along the chromosomes. Luzula sylvatica holocentromeres are predominantly associated with two satellite DNA repeats (Lusy1 and Lusy2), while CENH3 also binds satellite-free gene-poor regions. Comparative repeat analysis suggests that Lusy1 plays a crucial role in centromere function across most Luzula species. Furthermore, synteny analysis between L. sylvatica (n = 6) and Juncus effusus (n = 21) suggests that holocentric chromosomes in Luzula could have arisen from chromosome fusions of ancestral monocentric chromosomes, accompanied by the expansion of CENH3-associated satellite repeats.